O projeto da Mensagem de Luanda e o seu número de estreia - Topa, Francisco (2023)
After an introduction about literary journals of modernism and the differences between European and American ones and those from Africa, the article considers the Angolan periodical Mensagem, published in Luanda in 1951-1952 by the Associação dos Naturais de Angola. Drawing attention to some of the aspects of the journal that remain to be studied, the author adds some information about the difficulties of printing the second issue and reviews the non-consensual historical assessment that has been made of the journal. That said, he analyses the first issue in some detail, focusing on the project of the publication and the texts included therein. In conclusion, he recognizes the decisive role of Mensagem in the break with colonial literature and in the affirmation of an Angolan literature.